Perancangan Interior Rumah Tinggal Tipe 100, 180, 280 Dengan Pendekatan Future Integration Living - Hendianto, Yehezkiel (Intra, 2017)
There are a lot of members of the society, both young and old, who are physically disabled or limited, so they have a little motion space even in their own homes. That condition has resulted in their inability to do physical activities, to be independent, and even to live with their family members as the latter choose to admit them to nursery homes with intensive care to meet their needs. Regarding the existing problem, this design is used to seek for a solution so that old and young generations can always live together in any condition and that users with physical limitations and the elderly can live together with their family members independently. It is hoped that the existence of this design can realize a safer, more comfortable and flexible home for everyone. The method for this last project is using design thinking from define the problem, observation, analyze, ideas, prototype, until implementation using social media like facebook, instagram, and line with posting photos or video that describe clearly and detail about this desain.